Dietary supplementation with Lactobacilli improves emergency granulopoiesis in protein-malnourished mice and enhances respiratory innate immune response. - Matias Herrera; Susana Salva; Julio Villena; Natalia Barbieri; Gabriela Marranzino; Susana Alvarez (PLoS ONE)
This work studied the effect of protein malnutrition on the hemato-immune response to the respiratory challenge with Streptococcus pneumoniae and evaluated whether the dietary recovery with a probiotic strain has a beneficial effect in that response. Three important conclusions can be inferred from the results presented in this work: a) protein-malnutrition significantly impairs the emergency myelopoiesis induced by the generation of the innate immune response against pneumococcal infection; b) repletion of malnourished mice with treatments including nasally or orally administered Lactobacillus rhamnosus CRL1505 are able to significantly accelerate the recovery of granulopoiesis and improve innate immunity and; c) the immunological mechanisms involved in the protective effect of immunobiotics vary according to the route of administration. The study demonstrated that dietary recovery of malnourished mice with oral or nasal administration of L. rhamnosus CRL1505 improves emergency granulopoiesis and that CXCR4/CXCR12 signaling would be involved in this effect. Then, the results summarized here are a starting point for future research and open up broad prospects for future applications of probiotics in the recovery of immunocompromised malnourished hosts.